Pemanfaatan Limbah Tempe Menjadi Media Tanam dan Pupuk Organik Cair (POC) yang Bernilai Ekonomi di Kelurahan Putat Jaya - Hanafilah Chayatul Fatihah; Erlita Alif Mawadah; Hadri Yanti Azizah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
One of the UMKM in Putat Jaya Village is Tempe Bang Jarwo UMKM. Tempe Bang Jarwo UMKM produces Tempe to be sold to various grocery stores and markets located in Put Jaya Village, in Tempe Bang Jarwo UMKM has problems with tempe waste, namely soybean skin dregs and water used to wash soybean skins, soybean skin waste will be sold to be used as animal feed, but the production of soybean husk waste is more than those who buy it, so if the soybean husk waste is still there it will be thrown away as well as the water used for washing soybean skin. Instead of being disposed of carelessly and causing environmental pollution, tempe waste will be processed into planting media for soybean husk waste and liquid organic fertilizer (POC) for wastewater used for washing soybean skins. Planting media and liquid organic fertilizer (POC) provide additional income for the processors, namely the tempe Bang Jarwo UMKM and the surrounding community. Routine training and assistance continue to be carried out so that the Tempe Bang Jarwo UMKM as well as the surrounding community can achieve results and have independence in the production of planting media and liquid organic fertilizer (POC) that are suitable for sale to meet market needs.